Realizing reparative justice for international crimes : from theory to practice / Miriam Cohen. - Cohen, Miriam, 1983- (Cambridge University Press, 2020)
This book provides a timely and systematic study of reparations in international criminal justice, going beyond a theoretical analysis of the system established at the International Criminal Court (ICC). It originally engages with recent decisions and filings at the ICC relating to reparation and how the criminal and reparative dimensions of international criminal justice can be reconciled. This book is equally innovative in its extensive treatment of the significant challenges of adjudicating on reparations, and proposing recommendations based on concrete experiences. With recent and imminent decisions from the ICC, and developments in national courts and beyond, Miriam Cohen provides a critical analysis of the theory and emerging jurisprudence of reparations for international crimes, their impact on victims and stakeholders.